Comparison of earthquake emergency management system in China and Japan - Zhongzhi Min; Xiaojun Li; Mianshui Rong (地震科学进展)
China has been making every effort to enhance the government’s emergency management capacity since 2003, and has formed an emergency management system with unified leadership, comprehensive coordination, classified management, hierarchical responsibility, territorial management and public participation. The emergency management system established with the basic framework of “one plan and three systems” has achieved remarkable practical results，and the National Earthquake Emergency Plan has been issued. This paper discussed the emergency management system in China and Japan, involving emergency plan and emergency management system, and showed the necessity of centralized administrative power to deal with the major earthquakes, and highlighted the characteristics of concentrating resources to do key things. This study revealed the unique advantages of China’s emergency management system in dealing with earthquakes from the perspectives of geographical conditions and national culture, and explained the reason why Japan’s emergency management system cannot form a unified leadership. At the same time, drawing lessons from the experience accumulated by Japan in the development of earthquake emergency management, the shortcomings of the current China’s earthquake emergency management system were pointed out, and suggestions were put forward for the development of China’s earthquake emergency management, providing reference for the improvement of China’s earthquake emergency management system.